PERJANJIAN ALLAH DENGAN BANI ISRAEL DI GUNUNG SINAI (STUDI KOMPARASI ANTARA AL-QUR’AN DAN ALKITAB) - Elma Sintia; Muhammad Taufiq (Adisam Publisher, 2025)
Today the story of the Children of Israel is still a hot topic among the people. The background is the issue of its naming and genealogy which is linked to Israel today, as well as because its story is immortalized in the Koran and the Bible as a condition for wisdom and lessons. The children of Israel have been a people of the covenant since their ancestor, the Prophet Abraham (AS). continued to the subsequent Prophets whom Allah sent to them. However, the Mount Sinai agreement was a very special agreement, because they could meet and talk directly to Allah and Allah gave them His words through the intermediary of the Prophet Musa (a.s.). This is what is interesting about the Mount Sinai agreement. so the author took the title God's Covenant with the Children of Israel at Mount Sinai. This type of research is qualitative with library research, while the comparative study is the author's effort to find common ground, other points and the value of God's covenant with the Children of Israel at Mount Sinai as contained in the Koran and the Bible. The Koran and Tafsir and the Bible and Tafsir are the main sources of research. The results of this research will show that there are not many similarities in the process of receiving God's word, and almost all of God's words in the Koran and the Bible show similarities. Meanwhile, prominent differences are found in the process of receiving God's word and few are found in the content of God's word. The value of obedience is the main value in this topic and is the key to God's strictness towards them. Obedience will give them God's love while their disobedience will give them God's wrath.